PENGARUH CITRA MEREK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PENGGUNAAN (Studi pada Penumpang Bis PO. Nusantara Kelas Eksekutif SemarangJakarta) - Indra Sulistyowardhana; Sudharto P Hadi (Universitas Diponegoro, 2017)
The increasing of people’s mobility encourages the high demand for transportation services. The competition between modes of transportation specially land transportation is very keen. One of transportations that became the choice of Indonesian people to do their activities is a bus. The number of PO. Nusantara’s passengers has decreased since 2014 – 2016. In 2014 to 2015 the number of passenger decreased by 5.01% and in 2015 to 2016 decreased by 6.34%. This study is aimed to identify the effect of brand image and service quality to decision of using P.O Nusantara executive class by route of Semarang-Jakarta. The type of research is explanatory research. The sample used is 100 respondents. The sampling techniques is purposive and accidental sampling. The technique analysis are crosstab, simple linear regression, multiple linear regression, t test and F test with the SPSS program. The result showed that there is a positive influence between brand image and service quality toward usage decision. Based on the results of simple regression analysis, it is known that brand image has influence on usage decision with coefficient of 0,229, while service quality influence usage decision of 0.100. This research recommends PO. Nusantara to strengthen its brand image by renewing the bus design so that consumers are able to clearly distinguish bus of PO. Nusantara with competitor bus. Improvements of service quality are also required, especially the timeliness of departure and arrival time, and also the cleanliness and cosiness of the departure lounge.